Untangling Challenges and Opportunities: Overcoming Toxic Leadership in Public Organizations in Donggala Regency - Daswati, Daswati; Hattab, Syahruddin; Rachmad, Rachmad; Ruslan, Alfionita (Program Pascasarjana Universitas Negeri Makassar, 2024)
Toxic leadership within public organizations poses significant challenges, particularly in regions like Donggala Regency, where effective governance is critical for public welfare. This study investigates the complexities of toxic leadership in public organizations in Donggala, focusing on the dual aspects of challenges and opportunities for mitigating its impact. The primary objective is to identify the specific leadership behaviors that contribute to a toxic environment and explore potential strategies to counteract these behaviors, thereby enhancing organizational performance and employee well-being. Utilizing a qualitative research approach, this study involves in-depth interviews with key stakeholders within public organizations in Donggala Regency, including employees, managers, and external observers. The data collected is analyzed using thematic analysis to uncover recurring themes related to toxic leadership and the existing mechanisms to address it. The findings reveal that while toxic leadership significantly hampers organizational efficiency and morale, there are untapped opportunities for intervention, such as leadership training programs and the establishment of more robust reporting mechanisms. The study concludes that a comprehensive understanding of toxic leadership's roots and effects is essential for developing targeted strategies to foster healthier organizational cultures. These insights are valuable not only for Donggala Regency but also for other public organizations facing similar challenges, providing a framework for leadership improvement and organizational reform.